2012
DOI: 10.1016/j.rmed.2012.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Dose effect of once-daily fluticasone furoate in persistent asthma: A randomized trial

Abstract: FF 50-200 μg/day once daily in the evening demonstrated dose-related efficacy in asthma with 100-200 μg appearing to be the optimal doses for further evaluation. ClinicalTrials.gov: NCT00603382.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
50
4
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 28 publications
9
50
4
2
Order By: Relevance
“…Phase IIb dose-ranging trials of VI in COPD [12] and FF in asthma [13][14][15] have shown that both therapies are efficacious and exhibit a once-daily dosing profile [16,17]. FF/VI has been studied at strengths of 50/ 25 mg, 100/25 mg and 200/25 mg in a small 4-week crossover study [18], and in larger 24-week lung function studies [19,20] and 52-week exacerbation studies [21]; none of these studies compared FF/VI with an established ICS/LABA combination, such as FP/SAL.…”
Section: Introductionmentioning
confidence: 99%
“…Phase IIb dose-ranging trials of VI in COPD [12] and FF in asthma [13][14][15] have shown that both therapies are efficacious and exhibit a once-daily dosing profile [16,17]. FF/VI has been studied at strengths of 50/ 25 mg, 100/25 mg and 200/25 mg in a small 4-week crossover study [18], and in larger 24-week lung function studies [19,20] and 52-week exacerbation studies [21]; none of these studies compared FF/VI with an established ICS/LABA combination, such as FP/SAL.…”
Section: Introductionmentioning
confidence: 99%
“…This was demonstrated in a study of moderate asthmatics [41]. Several studies have demonstrated the efficacy and safety of this drug in asthma patients in dosages of 50 --400 µg daily [42][43][44][45]. However, a randomized controlled trial investigating the efficacy of a small dose of 50 µg once daily in mild to moderate asthmatics did not show a significant change in the primary endpoint (FEV1) compared with placebo after 24 weeks of treatment [46].…”
Section: Market Reviewmentioning
confidence: 98%
“…Doses of FF between 25 and 200 µg OD and FP 100 µg BD and placebo were compared for 8 weeks in patients with persistent asthma [31]. Doses of FF greater than 50 µg OD significantly increased the FEV 1 compared with placebo, with doses of 100 and 200 µg increasing the FEV 1 by greater than 200 mL.…”
Section: Phase I and Ii Efficacy Studiesmentioning
confidence: 99%